1983
DOI: 10.1159/000241729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cholecystokinin Octapeptide and Hydrocortisone on the Development of Fetal Rat Pancreas

Abstract: Mechanisms and development of pancreas and pancreatic secretory function were studied in the rat. Injections of cholecystokinin octapeptide and hydrocortisone into pregnant rats altered pancreatic size, zymogen enzyme, and DNA content in the fetal newborn pancreas. These studies suggest that the developmental signals for pancreatic function may be related to endogenous release of cholecystokinin or hydrocortisone in the perinatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…It has been suggested that some gastrointestinal peptides and classical endocrine glands may interact in the regulation of pancreatic growth and that of the gas trointestinal mucosa [Enochs and Johnson. 1977;Werlin andStefaniak. 1983: Johnson.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that some gastrointestinal peptides and classical endocrine glands may interact in the regulation of pancreatic growth and that of the gas trointestinal mucosa [Enochs and Johnson. 1977;Werlin andStefaniak. 1983: Johnson.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a 4-day treatment of hydrocortisone to females at the end of their pregnancy had no effect on fetal pancreas growth [11], while a 10-day [9] or a 21-day treatment (this study) caused significant fetal pancreas growth. The effect is also dose dependent, as shown in this study with hyperplasia observed only with the highest dose.…”
Section: Discussionmentioning
confidence: 49%
“…Such an effect, although previously observed by Werlin and Stefaniak [11], cannot be ascribed to occupation of the CCK A receptors, because their mRNA expression is minimal in the rat fetal pancreas [6]. If the fetal guinea pig pancreas expresses a majority of CCK B receptor mRNAs, as the fetal rat pancreas does, this would explain the lack of effect of the CCK A receptor antagonist MK329 given during the entire pregnancy to guinea pigs on fetal pancreatic weight and total protein, RNA, and DNA contents [12].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations